2021
DOI: 10.3389/fgene.2021.812509
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crucial Genes and Infiltrating Immune Cells Underlying Sepsis-Induced Cardiomyopathy via Weighted Gene Co-Expression Network Analysis

Abstract: Sepsis-induced cardiomyopathy (SIC), with a possibly reversible cardiac dysfunction, is a potential complication of septic shock. Despite quite a few mechanisms including the inflammatory mediator, exosomes, and mitochondrial dysfunction, having been confirmed in the existing research studies we still find it obscure about the overall situation of gene co-expression that how they can affect the pathological process of SIC. Thus, we intended to find out the crucial hub genes, biological signaling pathways, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…From the published articles, we also found that Chen et al ( 61 ), Kang et al ( 62 ), Gong et al ( 63 ), Li et al ( 64 ), and Wang et al ( 65 ). similarly applied bioinformatics approaches to study the hub genes in SCM.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…From the published articles, we also found that Chen et al ( 61 ), Kang et al ( 62 ), Gong et al ( 63 ), Li et al ( 64 ), and Wang et al ( 65 ). similarly applied bioinformatics approaches to study the hub genes in SCM.…”
Section: Discussionmentioning
confidence: 57%
“…similarly applied bioinformatics approaches to study the hub genes in SCM. First and foremost, our studies with Chen et al ( 61 ), Kang et al ( 62 ), Li et al ( 64 ), and Wang et al ( 65 ) used the human SCM dataset GSE79962 as an experimental dataset, but we innovatively combined immune cell marker genes with SCM differentially expressed genes to identify the biomarker role of IRHG in SCM; Secondly, we also used MCODE to identify the central clusters of SCM differentially expressed genes to explore modules that play an important interaction in SCM and their involved pathways; Thirdly, different from the studies of Kang et al ( 62 ) and Gong et al ( 63 ), we also extracted human samples to verify the expression of target genes, and used ROC curves to analyze the diagnosticity of target genes for SCM. Finally, a miRNA-IRHG pair that is different from previous studies and has an immunomodulatory role in SCM was obtained: miR-222-3p/THBS1.…”
Section: Discussionmentioning
confidence: 59%
“…In a recent bioinformatics analysis of sepsis-induced cardiomyopathy, POR was selected as the central gene and its expression level was higher than that of the control group. GSEA then demonstrated POR to have a close relationship with cardiac metabolism, necroptosis and apoptosis of cells in SIC ( Li et al, 2021 ). Solute carrier family 7 member 5 (SLC7A5), also known as L-type amino acid transporter (LAT1) ( Galluccio et al, 2013 ), is a sodium-independent high-affinity amino acid transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, necroptosis triggers inflammation and immunogenic events in different diseases by interacting with death receptors and diverse cytoplasmic protein kinases. Unlike necrosis, which usually results in irreversible pathological damage, necroptosis is employed by organisms to acquire appropriate levels of energy supply and promote cell regeneration 179,180 . Initially, defined as a type of TNF‐induced necrosis, necroptosis was subsequently recognized as a specific kinase‐dependent process after being effectively subdued by RIPK1 inhibitors 181–183 .…”
Section: Regulatory Mechanisms Involved In Sepsismentioning
confidence: 99%